Nonlinear solid electrolyte membrane material, preparation method, membrane and device
By introducing specific structures and compositions into the nonlinear solid electrolyte membrane material, the decomposition and swelling problems under high temperature and strong alkaline conditions are solved, and a high-performance nonlinear solid electrolyte membrane material is achieved, with low swelling, high ionic conductivity and high Alkaline stability.
Patent Information
- Application Number
- CN202411264838.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing nonlinear solid electrolyte membrane materials are easily decomposed under high temperature and strong alkaline conditions, resulting in poor stability for a long time. The linear solid electrolyte membrane materials are easily swelled after soaking in solvents, affecting durability.
Using nonlinear solid electrolyte membrane materials containing linear structures and crosslinked structures, the benzene derivatives, carbazole derivatives and alkyl substituent groups are composed of charges, combined with side chain groups and hydrophobic structural groups. The group was synthesized using solvents such as triflate and sulfonic acid, and was soaked in potassium carbonate solution and reacted with DMSO to obtain high-performance film materials.
A nonlinear solid electrolyte membrane material with low swelling, high ionic conductivity and high alkali stability is achieved, which improves the durability and electrochemical performance of the membrane.
Smart Images

Figure CN119133542A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid electrolytes, and in particular relates to a nonlinear solid electrolyte membrane material, a preparation method, a membrane and a device. Background Art
[0002] Anionic solid electrolyte membrane materials play an important role in the fields of water electrolysis, electrodialysis, flow batteries and fuel cell technology. Linear solid electrolyte membrane materials will swell after being immersed in solvents for a long time. The dimensional change often leads to local stress differences in the system, resulting in changes in the durability of the membrane. Nonlinear solid electrolyte membranes perform better in terms of anti-swelling. The traditional method of using polyhalogenated hydrocarbons or polyamine compounds to construct nonlinear solid electrolyte membranes often introduces quaternary ammonium salt structural units, which may decompose under high temperature and strong alkaline conditions, thereby affecting the long-term stability of the membrane. Therefore, it is of great value to develop new nonlinear solid electrolyte polymer membrane materials with low swelling, high ionic conductivity and high alkaline stability.
[0003] Therefore, in view of the above technical problems, it is necessary to provide a nonlinear solid electrolyte membrane material, preparation method, membrane and device.
[0004] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention
[0005] The object of the present invention is to provide a nonlinear solid electrolyte membrane material, a preparation method, a membrane and a device.
[0006] It should be noted that: in the expression of the structural formula or structural simplified formula of the present invention, and Both refer to substitution sites or active sites.
[0007] In order to achieve the above object, a technical solution provided by a specific embodiment of the present invention is as follows:
[0008] The main raw materials of nonlinear solid electrolyte membrane materials include the following two structures:
[0009] a. Linear structure Where m and n are positive integers, Ar 1 and Ar 2 The main body is independently selected from benzene, biphenyl, p-terphenyl, m-terphenyl, o-terphenyl, p-quaterphenyl, m-quaterphenyl, pentylene, 1,2-diphenylethane, 3,3'-dimethylbiphenyl, fluorene and its derivatives having at least one alkyl substituent, carbazole and its N-alkylcarbazole derivatives, anthracene, phenanthrene, naphthalene, R1 Selected from charged side chain groups, R 2 Selected from hydrophobic structural groups;
[0010] b. A cross-linked structure, wherein the main unit is selected from (where the number of sites in the corresponding structures are 4, 4, 3, 3, 6, 3, i.e. the number of pairs of benzene rings in each unit);
[0011] The ratio of the number of cross-linked structural sites to the total number of structural sites is 0.01%-15%. 1 Number of sites, Ar 2 The total number of sites and the number of cross-linked structure sites. The number of sites can be regarded as functionality. Preferably, the derivatives of the alkyl substituent of the fluorenyl group can be selected from methyl, dimethylfluorene and ethyl or more other alkyl substituted derivatives. N-alkyl carbazole derivatives can be selected from N-methyl carbazole, N-ethyl carbazole, etc. Preferably, the substitution position of the derivative is at least position 9.
[0012] In one or more embodiments of the present invention, the charged side chain group is a side chain group having an ammonium salt.
[0013] In one or more embodiments of the present invention, the charged side chain group is selected from piperidinium or quinuclidine or quaternary ammonium salts.
[0014] In one or more embodiments of the present invention, the charged side chain groups are selected from:
[0015]
[0016] Where R 3 , R 4 , R 5 , R 8 , R 9 , R 10 , R 13 R is independently selected from one or more of an alkyl group, an aryl group, or an alkyl group or an aryl group substituted with halogen; 6 , R 11 independently selected from alkyl or halogen-substituted alkyl;
[0017] R 7 , R 12 are independently selected from alkyl or aryl; X is an anion. It only represents the symbol of the anion, and does not represent the valence state of the anion. Preferably, X is a halogen ion. When the anion is a carbonate, bicarbonate, hydroxide, sulfate, sulfonate, etc., it can be obtained by soaking and replacing the corresponding solution.
[0018] In one or more embodiments of the present invention, the anion is selected from halogen ion, carbonate, bicarbonate, hydroxide, trifluoromethanesulfonate, trifluorobenzenesulfonate anion, phosphorus hexafluoride anion, boron tetrafluoride anion, sulfate, sulfonate, nitrate.
[0019] In one or more embodiments of the present invention, the hydrophobic structural group is Where R 16 and R 17 are independently alkyl, aryl, alkyl substituted by halogen, or aryl substituted by halogen, and R 16 and R 17 At least one of them is F or fluorine substituted group.
[0020] In one or more embodiments of the present invention, the hydrophobic structural group is Where R 18 -R 22 are independently selected from hydrogen, alkyl, aryl, halogen, halogen-substituted alkyl, halogen-substituted aryl, R 18 -R 22 Preferably H or F. Preferred R 16 It is trifluoromethyl.
[0021] In one or more embodiments of the present invention, a method for preparing a nonlinear solid electrolyte membrane material is characterized by comprising:
[0022] The raw material monomer is dissolved in the solution, and trifluoromethanesulfonic acid is slowly added under ice bath conditions to react to obtain a viscous solution;
[0023] Slowly add the viscous solution dropwise into water or alcohol solution to precipitate solid;
[0024] The solid is immersed in a potassium carbonate solution and stirred, washed and dried, and then DMSO and a salt-forming small molecule are added to react to obtain a reaction product. Preferably, the alcohol solution is a mixture of alcohol and water in any ratio. The alcohol can be a monohydric alcohol or polyhydric alcohol with a C5 or lower content such as methanol and ethanol.
[0025] In one or more embodiments of the present invention, the electrolyte membrane is: a membrane formed by a first casting solution made of a nonlinear solid electrolyte membrane material and / or an additive; or a membrane formed by combining a second casting solution made of a nonlinear solid electrolyte membrane material and / or an additive with a support layer. The preferred support layer can be a porous support structure, such as a porous membrane or a mesh.
[0026] In one or more embodiments of the present invention, the device having ion conduction function includes an electrode, and the electrode includes an electrolyte membrane. The device is mainly used in electrochemical fields such as alkaline water electrolysis, fuel cells, electrodialysis, flow batteries, and electrochemical energy storage.
[0027] Compared with the prior art, the nonlinear solid electrolyte membrane material, preparation method, membrane and device of the present invention are simple to prepare and have high ion conductivity, while having low swelling and high ion conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 is the NMR graph of the polymer in Example 1 of the present invention;
[0030] Figure 2 is the NMR graph of the polymer in Example 18 of the present invention;
[0031] Figure 3 is the NMR graph of the polymer in Example 19 of the present invention;
[0032] Figure 4 This is a graph showing the ion conductivity test of the polymer taken out after different time periods in Example 1 of the present invention;
[0033] Figure 5 Graphs showing the ionic conductivity and swelling of polymers at different temperatures in an embodiment of the present invention. DETAILED DESCRIPTION
[0034] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0035] The preparation process comprises the following steps in sequence:
[0036] a) Synthesis of ion-conducting polymer compositions
[0037] One method is: dissolving aromatic compound monomer units, ketone-containing monomer units, fluorine-containing ketone structural units, and crosslinking agent structural units in a dichloromethane or trichloromethane solution. The molar ratio of aromatic monomer to ketone-containing monomer is 1:0.8 to 1:2, slowly adding trifluoromethanesulfonic acid under ice bath conditions, wherein the equivalent of trifluoromethanesulfonic acid is 1-10 times the molar amount of aromatic compound, reacting at 0-80 degrees for 1-48 hours, obtaining a viscous solution, slowly dripping into an ethanol solution, and precipitating a solid. Soaking in 1M potassium carbonate and stirring for 1-24 hours, filtering and drying, taking 1g of the solid, adding 20ml of DMSO, adding 0.5-10 times the molar amount of aromatic monomer equivalents of molecular units for salt formation (including monohalogenated hydrocarbon compounds or polyhalogenated hydrocarbon compounds or amine compound small molecules), reacting at room temperature for more than 4 hours, dripping the obtained solution into ethyl acetate to obtain a solid product, and drying at 60 degrees to obtain the final high molecular polymer. Dissolve 1 g of polymer in 20 ml of DMSO solution to obtain the slurry required for film formation.
[0038] The second method is as follows: other additives may be added to the solution of the above scheme to form a slurry, that is, a casting solution. The additives here may be inorganic hydrophilic oxides, etc. The inorganic hydrophilic oxides are selected from one or more of zirconium oxide, titanium dioxide, barium sulfate, magnesium hydroxide, zinc carbonate, nickel hydroxide, and hydrotalcite materials, preferably zirconium oxide and barium sulfate. The inorganic hydrophilic oxide particles have a size between 1nm and 1μm, preferably between 5nm and 500nm. The inorganic hydrophilic oxide accounts for 0-60% of the mass fraction of the polymer, preferably in the range of 10-30%.
[0039] c) Preparation of anion exchange membrane
[0040] Anion exchange membranes are divided into three categories
[0041] (1) Directly cast the casting liquid onto a flat substrate. The material of the flat substrate can be PE, PET, PP, PTFE, glass, etc., among which PET is preferred. Dry at 80°C to form a film.
[0042] (2) Lay the porous support layer evenly on the glass substrate. The porous support layer is selected from polypropylene (PP), polyethylene (PE), polysulfone (PS), polyphenylene sulfide (PPS), polyamide / nylon (PA), polyethersulfone (PES), polyphenylene sulfone (PPS), polyethylene terephthalate (PET), polyetheretherketone (PEEK), sulfonated polyetheretherketone (s-PEEK), expanded polytetrafluoroethylene (E-PTFE), chlorotrifluoroethylene (CTFE), copolymers of ethylene and tetrafluoroethylene (ETFE) or chlorotrifluoroethylene (ECTFE), polyimide, polyetherimide and meta-aramid (m-aramide) to prepare fabrics and non-woven fabrics, preferably EPTFE. The thickness of the porous support layer is 1-60μm, preferably 2μm-40μm. The porosity of the porous support layer is 40-90%, preferably 50-80%. Use a Meyer rod to evenly coat the casting solution on the ePTFE, then put it into an 80°C oven for drying and then take it out.
[0043] (3) Mix the casting solution obtained above with an appropriate amount of additives such as inorganic hydrophilic oxides. Then the mixed casting solution can be directly cast onto a flat substrate, the material of which can be PE, PET, PP, PTFE, glass, etc., preferably PET, or coated onto a porous support layer by a Meyer rod. Dry at 80°C to form a film.
[0044] Including but not limited to the following embodiments, the ethanol solution can be directly replaced by any monohydric alcohol or polyhydric alcohol below C5 or any mixture of the aforementioned alcohol and water, or water, without affecting the implementation of the technical solution of the present application.
[0045] Example 1: (0.5%)
[0046] Mix terphenyl, N-methylpiperidone, tetraphenylene and dichloromethane, the amount of terphenyl is 2.29g, the amount of N-methylpiperidone is 1.13g, the amount of tetraphenylene is 8.31mg, and the amount of dichloromethane is 7ml. Slowly add trifluoromethanesulfonic acid under ice bath conditions, wherein the amount of trifluoromethanesulfonic acid is 7ml, react in an ice bath for 24h to obtain a viscous solution, slowly drip into a 20v / v% ethanol solution, and precipitate a solid. Soak in 1M potassium carbonate and stir for 8 hours, filter and dry, take 1g of the solid, add 20ml of DMSO, add 1.69g of iodomethane, and react at room temperature for 12h. The obtained solution is dripped into ethyl acetate to obtain a solid product, which is dried at 60 degrees to obtain the final polymer. Dissolve 1g of polymer in 20ml of DMSO solution to obtain the slurry required for film formation. Cast the casting solution directly onto glass. Dry at 80℃ to form a film.
[0047]
[0048] like Figure 1 As shown, 7.61-7.73ppm are the aromatic signals on the benzene ring in terphenyl, and the signal of tetraphenylethylene overlaps there, 3.42ppm is the signal of hydrogen at position 1, which slightly overlaps with the signal of the water peak in deuterated DMSO, 3.17ppm is the signal at position 3, 2.91ppm is the hydrogen signal at position 2, 2.50ppm is the signal of deuterated DMSO, and 2.55ppm is the signal of solvent DMSO.
[0049] Example 2: (0.1)
[0050] The difference from Example 1 is that the amount of terphenyl is 2.30 g and the amount of tetraphenylethylene is 1.66 mg.
[0051] Embodiment 3: (1)
[0052] The difference from Example 1 is that the amount of terphenyl is 2.28 g and the amount of tetraphenylethylene is 16.6 mg.
[0053] Example 4: (5%)
[0054] The difference from Example 1 is that the amount of terphenyl is 2.18 g and the amount of tetraphenylethylene is 83.1 mg.
[0055] Example 5: (10%)
[0056] The difference from Example 1 is that the amount of terphenyl is 1.96 g, and the amount of tetraphenylethylene is 249.3 mg.
[0057] Example 6: (15%)
[0058] The difference from Example 1 is that the amount of terphenyl is 1.84 g, and the amount of tetraphenylethylene is 332 mg.
[0059] Embodiment 7:
[0060] The difference from Example 1 is that tetraphenylethylene is replaced by triptycene in an amount of 25.4 mg.
[0061]
[0062] Embodiment 8:
[0063] The difference from Example 1 is that tetraphenylethylene is replaced by tetraphenylmethane, and the amount used is 8.01 mg.
[0064]
[0065] Embodiment 9:
[0066] The difference from Example 1 is that tetraphenylethylene is replaced by triphenylbenzene, and the amount used is changed to 10.21 mg
[0067]
[0068] Embodiment 10:
[0069] The difference from Example 1 is that tetraphenylethylene is replaced with 9,10-triphenylene and the dosage is changed to 7.6 mg
[0070]
[0071] Embodiment 11:
[0072] The difference from Example 1 is that p-terphenyl is replaced by diphenyl, and the amount of diphenyl used is 1.46 g.
[0073] Embodiment 12:
[0074] The difference from Example 1 is that p-terphenyl is replaced by 1.15 g m-terphenyl and 1.15 g p-terphenyl.
[0075] Embodiment 13:
[0076] The difference from Example 1 is that p-terphenyl is replaced by 1.15 g and 1.09 g of 9,9-dimethylfluorene.
[0077] Embodiment 14:
[0078] The difference from Example 1 is that an expanded polytetrafluoroethylene membrane (E-PTFE) with a thickness of 10 μm is evenly spread on a glass substrate, the obtained slurry is poured on it, and dried at 80° C. for 12 hours to form a thin film substance with fillers in the pores of the expanded polytetrafluoroethylene membrane.
[0079] Embodiment 15:
[0080] The difference from Example 1 is that: 0.1 g of 30 μm zirconium oxide powder is added to the obtained slurry, stirred evenly to obtain a heterogeneous slurry, a 10 μm thick expanded polytetrafluoroethylene membrane (E-PTFE) is evenly spread on a glass substrate, the obtained heterogeneous slurry is poured on it, and dried at 80°C for 12 h to form a film
[0081] Embodiment 16:
[0082] The difference from Example 1 is that N-methylpiperidone is replaced by 3-quinuclidinone, the amount used is 1.482 g, and the reaction is carried out at room temperature for 48 hours.
[0083]
[0084] Embodiment 17:
[0085] The difference from Example 1 is that N-methylpiperidone is replaced by 4-trifluoroacetylbenzyl bromide (CAS: 78126-14-4) in an amount of 1.482 g, and methyl iodide is replaced by 30% ethanol solution of trimethylamine in an amount of 2.36 g.
[0086]
[0087] Embodiment 18:
[0088] The difference from Example 1 is that 1-(3,5-difluorophenyl)-2,2,2-trifluoroethanone is added in an amount of 0.315 g, and the piperidone equivalent is adjusted to 0.96 g.
[0089]
[0090] like Figure 2 As shown, 7.39-7.83ppm are the aromatic signals on the benzene ring in terphenyl, 6.7999m is the signal of hydrogen at position 5, 7.22ppm is the signal of hydrogen at position 4, 3.39ppm is the signal of hydrogen at position 1, which slightly overlaps with the signal of the water peak in deuterated DMSO, 3.17ppm is the signal at position 3, 2.89ppm is the signal of hydrogen at position 2, and 2.50ppm is the signal of deuterated DMSO.
[0091] Embodiment 19:
[0092] The difference from Example 1 is that trifluoroacetophenone is added in an amount of 0.261 g, and the piperidone equivalent is adjusted to 0.96 g.
[0093]
[0094] like Figure 3 As shown, 7.45-7.85ppm is the aromatic signal on the benzene ring in terphenyl, 7.15-7.22 is the signal of hydrogen on the aromatic ring of trifluoroacetophenone, 3.35ppm is the signal of hydrogen at position 1, which slightly overlaps with the signal of the water peak in deuterated DMSO, 3.17ppm is the signal at position 3, 2.91ppm is the hydrogen signal at position 2, and 2.50ppm is the signal of deuterated DMSO.
[0095] Comparative Example 1
[0096] Mix terphenyl and N-methyl-4-piperidone, the amount of terphenyl is 2.3g, the amount of N-methyl-4-piperidone is 1.13g, and the amount of dichloromethane is 7ml. Slowly add trifluoromethanesulfonic acid under ice bath conditions, wherein the amount of trifluoromethanesulfonic acid is 7ml, react in an ice bath for 24h to obtain a viscous solution, slowly drip into an ethanol solution, and precipitate a solid. Soak in 1M potassium carbonate and stir for 8 hours. After filtering and drying, take 1g of the solid, add 20ml of DMSO, add 1ml of iodomethane, react at room temperature for 12h, and drip the obtained solution into ethyl acetate to obtain a solid product. Dry at 60 degrees to obtain the final polymer. Dissolve 1g of polymer in 20ml of DMSO solution to obtain the slurry required for film formation. Cast the casting solution directly onto glass. Dry at 80℃ to form a film.
[0097]
[0098] Comparative Example 2
[0099] Mix terphenyl and 3-quinuclidine ketone, the amount of terphenyl is 2.3g, the amount of 3-quinuclidine ketone is 1.24g, and the amount of dichloromethane is 7ml. Slowly add trifluoromethanesulfonic acid under ice bath conditions, where the amount of trifluoromethanesulfonic acid is 7ml, react at room temperature for 48h, obtain a viscous solution, slowly drip into an ethanol solution, and precipitate a solid. Soak in 1M potassium carbonate and stir for 8 hours. After filtering and drying, take 1g of the solid, add 20ml of DMSO, add 1ml of iodomethane, react at room temperature for 12h, and drip the obtained solution into ethyl acetate to obtain a solid product. Dry at 60 degrees to obtain the final polymer. Dissolve 1g of polymer in 20ml of DMSO solution to obtain the slurry required for film formation. Cast the casting solution directly onto glass. Dry at 80℃ to form a film.
[0100]
[0101] Electrochemical performance test
[0102] The hydroxyl ion conductivity test was performed using the Chenhua electrochemical workstation. The anion exchange membrane was soaked in 80-degree 1M KOH solution overnight for 12 hours, and then repeatedly washed with deionized water until the KOH solution on the surface was completely washed off. The 25-degree hydroxyl ion conductivity test was then performed using the four-probe method.
[0103] During the long-term test, the membrane was immersed in 80-degree 1M KOH solution for a long time and then taken out after different time periods for ion conductivity testing.
[0104] The test method of swelling performance is as follows: cut the prepared anion exchange membrane into square size (3cm×3cm) membrane samples, soak them in 80 degree 1M KOH solution for 12 hours, take out the membrane sample, quickly wipe the residual liquid on the surface of the membrane sample with filter paper, and measure the thickness T1 of the membrane sample. After that, bake the membrane sample at 60℃ for 0.5h, measure the thickness of the membrane sample in the dry film state, and record it as T2. The swelling rate of the anion exchange membrane is calculated as follows: Swelling rate = [(T1-T2) / T2]×100%.
[0105]
[0106] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
[0107] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A nonlinear solid electrolyte membrane material, the main raw materials of which include the following two parts: a. Linear structure wherein m is a positive integer, n is a natural number, Ar1 and Ar2 are independently selected from benzene, biphenyl, p-terphenyl, m-terphenyl, o-terphenyl, p-quaterphenyl, m-quaterphenyl, pentylene, 1,2-diphenylethane, 3,3'-dimethylbiphenyl, fluorene and its derivatives having at least one alkyl substituent, carbazole and its N-alkylcarbazole derivatives, anthracene, phenanthrene, naphthalene, R1 is selected from side chain groups with charges, and R2 is selected from hydrophobic structural groups; b. A cross-linked structure, wherein the main unit is selected from The mass ratio of the number of cross-linked structure sites to the total number of structure sites is 0.01%-15%, and the total number of structure sites is the sum of the number of Ar1 sites, the number of Ar2 sites and the number of cross-linked structure sites.
2. The nonlinear solid electrolyte membrane material according to claim 1, characterized in that: The side chain group with charge is a side chain group with ammonium salt.
3. The nonlinear solid electrolyte membrane material according to claim 2, characterized in that: The charged side chain group is selected from piperidinium or quinuclidine or quaternary ammonium salts.
4. The nonlinear solid electrolyte membrane material according to claim 3, characterized in that: The charged side chain groups are selected from: Among them, R3, R4, R5, R8, R9, R 10 , R 13 R6, R 11 are independently selected from alkyl or halogen-substituted alkyl; R7, R 12 are independently selected from alkyl or aryl; X is an anion.
5. The nonlinear solid electrolyte membrane material according to claim 4, characterized in that: The anion is selected from the group consisting of halogen ion, carbonate, bicarbonate, hydroxide, trifluoromethanesulfonate, p-trifluorobenzenesulfonic acid anion, phosphorus hexafluoride anion, boron tetrafluoride anion, sulfate, sulfonate, and nitrate.
6. The nonlinear solid electrolyte membrane material according to claim 1, characterized in that: The hydrophobic structural group is Where R 16 and R 17 are independently alkyl, aryl, alkyl substituted by halogen, or aryl substituted by halogen, and R 16 and R 17 At least one of them is F or fluorine substituted group.
7. The nonlinear solid electrolyte membrane material according to claim 6, characterized in that: The hydrophobic structural group is Where R 18 -R 22 Independently selected from hydrogen, alkyl, aryl, halogen, halogen-substituted alkyl, halogen-substituted aryl.
8. The method for preparing a nonlinear solid electrolyte membrane material according to any one of claims 1 to 7, characterized in that: include: The raw material monomer is dissolved in the solution, and trifluoromethanesulfonic acid is slowly added under ice bath conditions to react to obtain a viscous solution; Slowly drip water or alcohol solution into the viscous solution to precipitate solid; The solid is immersed in a potassium carbonate solution and stirred, and after washing and drying, DMSO and a salt-forming small molecule are added to react to obtain a reaction product.
9. An electrolyte membrane, comprising: a membrane formed by a first casting liquid made from the nonlinear solid electrolyte membrane material and / or additives described in any one of claims 1 to 7; or a membrane formed by combining a second casting liquid made from the nonlinear solid electrolyte membrane material and / or additives described in any one of claims 1 to 7 with a supporting layer. 10 . A device having an ion-conducting function, comprising an electrode, wherein the electrode comprises the electrolyte membrane according to claim 9 .
Citation Information
Patent Citations
Branched polyaryl piperidine polymer and anion exchange membrane
CN115521445A
Piperidine tertiary amine group polymer containing spatial three-dimensional crosslinking center carbon-based skeleton structure
CN116396469A
Anion exchange membrane containing aryl piperidine and benzenedione monomer copolymer as well as preparation method and application of anion exchange membrane
CN117510802A
Ion conduction polymer and preparation method thereof, ion conduction cross-linked substance and preparation method thereof, anion exchange membrane and application thereof
CN117603435A
Cationic polymer based on halogenated m-terphenyl group as well as preparation method and application of cationic polymer
CN118580470A
